2019
DOI: 10.24095/hpcdp.39.10.02
|View full text |Cite
|
Sign up to set email alerts
|

At-a-glance - Canadian Chronic Disease Indicators, 2019 – Updating the data and taking into account mental health

Abstract: The 2019 edition of the Canadian Chronic Disease Indicators (CCDI) provides recent estimates of the burden of chronic conditions and measures of general health and associated determinants in Canada. Using data from the CCDI and 2017 Canadian Community Health Survey, we explored the relationship between sociodemographic factors and selfreported mental health. Our findings suggest that sex (males vs females: adjusted odds ratio [aOR] = 1.22); age (65–79 vs 35–49 year age group: aOR = 1.48); education (postsecond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 8 publications
0
22
0
1
Order By: Relevance
“…Specifically, students who attended school in an urban area tended to report higher PSWB than students attending school in a rural area in the unadjusted model, with the opposite pattern found after adjustment. Given that previous Canadian research has found mixed evidence for differences in positive mental health outcomes in urban versus rural areas [50][51][52] and that associations between rural/urban school setting and psychological/social functioning were not consistently found across the sex-stratified analyses, we hesitate to consider school area to be a potentially important determinant of PSWB in Canadian youth.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, students who attended school in an urban area tended to report higher PSWB than students attending school in a rural area in the unadjusted model, with the opposite pattern found after adjustment. Given that previous Canadian research has found mixed evidence for differences in positive mental health outcomes in urban versus rural areas [50][51][52] and that associations between rural/urban school setting and psychological/social functioning were not consistently found across the sex-stratified analyses, we hesitate to consider school area to be a potentially important determinant of PSWB in Canadian youth.…”
Section: Discussionmentioning
confidence: 98%
“…Although chronic medical conditions are the primary cause of mortality in high-income countries, such as in Canada, these diseases affect low- and middle-income countries in a much higher proportion, with more than 75% of worldwide deaths from such diseases occurring in these nations ( 38 , 39 ). This is the case of Brazil, a middle-income country, where chronic diseases are also a leading health problem ( 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic medical conditions are a leading health problem in high-income countries, such as Canada, which has an estimated population of 37 million people ( 1 , 4 ). These medical conditions affect LMIC in an even higher proportion—with more than 75% of worldwide deaths from such diseases occurring in these nations ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the newest report, the last decade has not seen much improvement, and this rate is now about 10% greater ( 8 ). Part of this situation is due to the lack of success in tackling these diseases' risk factors, mainly physical inactivity (usually identified when one does not engage in at least 150 min of moderate to vigorous physical activity (PA) per week); unhealthy diet (often characterized when one eats less than five servings of fruits and vegetables per day); smoking (tobacco use in any dose or route); and harmful alcohol intake (commonly observed in irregular or chronic heavy drinking) ( 3 , 4 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation